Diagnosis of cytomegalovirus infection in heart transplant recipients. Issue 7 (July 1992) - Rice, P S; Kudesia, G; Price, C; Smith, G H
Abstract : In a prospective study eight (47%) heart transplant recipients had recurrent cytomegalovirus (CMV) infection. Of these, five had received hearts from seropositive donors. Neither serology nor virus isolation from urine was reliably associated with clinical CMV infection, but a high CMV IgM index correlated with CMV infection.